Takayasu’s Arteritis in Pregnancy: A Rare Case Report from a Tertiary Care Infirmary in India - Sheeba Marwah; Monika Rajput; Ritin Mohindra; Harsha S. Gaikwad; Manjula Sharma; Sonam R. Topden (Case Reports in Obstetrics and Gynecology)
Background. Takayasu’s arteritis (TA) is a rare, chronic, inflammatory, progressive, idiopathic arteriopathy, afflicting young women of reproductive age group, causing narrowing, occlusion, and aneurysms of systemic and pulmonary arteries, especially the aorta and its branches. During pregnancy, such patients warrant special attention. An interdisciplinary collaboration of obstetricians, cardiologists, and neurologists is necessary to improve maternal and fetal prognosis. Here a case is reported where a patient with diagnosis of TA, complicated by neurological sequelae, successfully fought the vagaries of the condition twice to deliver uneventfully. Case. 25-year-old G2P1L1 presented at 34 weeks of gestation, with chronic hypertension, with TA, with epilepsy, and with late-onset severe IUGR. Following a multidisciplinary approach, she delivered an alive born low birth weight baby (following induction). Her postpartum course remained uneventful. Conclusion. Pregnancy with TA poses a stringent challenge to an obstetrician. Despite advancements in cardiovascular management and advent of new-fangled drugs, the optimal management for pregnant patients with this disease still remains elusive.